Why do some coups lead to democratization?. Issue 5 (4th July 2022) - Zengin, Huseyin
ABSTRACT: Coups are forceful acts of removal staged against incumbent governments. Yet, the democratic coup hypothesis indicates the possibility of coup-led democratization. Do coups really lead to democratization? And if so, why do only some coups trigger a democratic transition? I analyse successful and failed coup events from 1950 to 2015 to address these questions, focusing on the mediating effects of domestic factors. The theoretical framework suggests that while successful coups lead to democratization in wealthier countries, high levels of income and state capacity allow authoritarian-leaning leaders to autocratize the country following a failed coup attempt. These findings have broader implications for civil–military relations and the international community's effect on military behaviour in post-coup settings.